11-8x=1-6x

Simple and best practice solution for 11-8x=1-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11-8x=1-6x equation:


Simplifying
11 + -8x = 1 + -6x

Solving
11 + -8x = 1 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
11 + -8x + 6x = 1 + -6x + 6x

Combine like terms: -8x + 6x = -2x
11 + -2x = 1 + -6x + 6x

Combine like terms: -6x + 6x = 0
11 + -2x = 1 + 0
11 + -2x = 1

Add '-11' to each side of the equation.
11 + -11 + -2x = 1 + -11

Combine like terms: 11 + -11 = 0
0 + -2x = 1 + -11
-2x = 1 + -11

Combine like terms: 1 + -11 = -10
-2x = -10

Divide each side by '-2'.
x = 5

Simplifying
x = 5

See similar equations:

| 3(5y-4)+15=5(y-3)-(3y+2) | | 12+3x=24-3x | | -20m+20=-17m-13 | | 20=12x+3 | | 5/6=x/6 | | 9x+(-7)=8x | | 10c=-11-3(-3c+1) | | -8r=-3r+20 | | x/6=0,5 | | 14v-12+7w+(-4v)= | | 20-y+20=2y-20 | | 6-0.5x=15 | | 9x+(17)=8x | | 8h+8=4h | | 18.75=3u | | 459.90=210x+1.19x | | 4=29+13x | | 6c=-8+2c | | -16-6-2g=-4(-g-20) | | y+3y-1=y | | -3g+4=9-8g | | 7x-x-10=-4 | | F(-4)=3x^2+5 | | 459.90=210x+119x | | 3=9+4c | | 14v+(-4v)= | | 5-2+8v=-9-4v | | y-7/16=-5/8 | | (-8x^6)^-4/3 | | 5-7w=-8w | | 459.90=210+119x | | x^2*x-20=0 |

Equations solver categories